On word order variation and informationstructure in peninsular spanish and italian ‘why’-interrogatives - Svenja Schmid (Universidade Estadual de Campinas, 2021)
In this paper, we investigate the effect of information structure on word order in Italian and Peninsular Spanish ‘why’-interrogatives, and whether these two languages differ from each other. To this end, we conducted two empirical studies. In a parallel text corpus study, we compared the frequency of the word order patterns ‘why’SV and ‘why’VS, as well as the distribution of focal and non-focal subjects in the two languages. In order to get a deeper understanding of the impact of the information structural categories focus and givenness on word order in ‘why’-interrogatives, we conducted a forced-choice experiment. The results indicate that word order is affected by focus in Italian, while it is not determined by any information structural category in Peninsular Spanish. We show that Italian and Peninsular Spanish ‘why’-interrogatives differ from each other in two ways. First, non-focal subjects occur preverbally in Italian, while they occupy the postverbal position in Peninsular Spanish. Second, Italian reveals a lower level of optionality with respect to word order patterns. Even though we find a high preference for the postverbal position in Peninsular Spanish, we argue that this limitation is related to a higher flexibility regarding word order in Peninsular Spanish than in Italian which does not allows for ‘why’VSO in contrast to Peninsular Spanish.